Rural internship in medical schools in Brazil - Ricardo de Lima Lacerda; Simone Appenzeller (2023)
Abstract: Introduction: The consolidation of rural internship programs is not a simple phenomenon, although its importance is currently recognized by students and teachers as a differentiated activity in their training itineraries. Medical schools still face considerable challenges in carrying out this type of activity. The existence of evidence that recruiting students to rural internships, offering meaningful experiences during undergraduate school and implementing a specific training program for rural areas after graduation, are the most effective interventions for recruitment and retention. Objective: Identify the rural internship programs in operation in Brazil, through the evaluation of Curricular Pedagogical Projects (PPCs,) of medical courses, fostering the debate on medical training for rural and remote areas, as well as emphasizing the importance of this type of training. Method: Cross-sectional, descriptive and documentary analysis study, with a quantitative characteristic, with a sampling of the access to the Curricular Pedagogical Projects (PPCs) of medical schools in Brazil with rural internships in the curriculum. Result: Of the 357 Medical Schools in Brazil, the authors found 18 programs with rural internships, corresponding to 5% of the institutions. The Southeast Region, when compared to the North region, concentrates the largest number of medical schools in Brazil (148), but the largest number of PPCs with rural internship is in the North Region of Brazil, totaling 6 (16%) in relation to medical schools in the region. Furthermore, of the 47 medical schools in the Southeast Region, in Minas Gerais, 2 rural internship programs were identified by the authors, in relation to other states in the same region. Conclusion: There are few rural internship programs identified in the PPCs in Brazilian medical schools. Changes are needed in the PPCs, with the inclusion of rural internships, with the inclusion of well-defined competencies and based on people’s health needs; construction of knowledge and development of skills and attitudes to solve problems, consistent with the reality of Brazil.